"Pegas" or "empachos" in Costa Rica and Central America. Historical and socioanthropological perspective of a folk disease - Campos Navarro, Roberto (2013)
Introduction. “Empacho” (or "pegas" in Costa Rica) is a popular constructed disease which refers to digestive system’s disorders due to stagnation or partial arrest of gastrointestinal transit.  Methods and Materials. A historical and anthropological review about this  pathological entity was made from 121 texts collected in public and private libraries around the region.  Results. Many files about “empacho” exist in Central America since the sixteenth century to our days. The concept, the epidemiology and prophylaxis, etiology, signs and symptoms, even treatments are similar from Guatemala to Panama. Discussion and conclusions.  “Empacho” is widely recognized by the popular and native people in Central  America. At least within bibliographical references, it is more frequent in Guatemala, Nicaragua, and Costa Rica. Every country along the region has shown an important conflict between folk medicine and biomedicine, it has been underestimated by academic physicians that approach it as any other digestive disorder such as dyspepsia, irritable bowel syndrome, intestinal obstruction, or gastrointestinal infection. “Empacho” is still, a long-lived and day-to-day health problems.